RECALLING STUDENT TEACHER’S BELIEFS ON ENGLISH LANGUAGE TEACHING: EVIDENCE FROM A PRE-SERVICE TEACHING PROGRAM IN INDONESIA - Della Putri Kandilla; Febi Pebriyani; Sinta Sri Meliana; Arbiansah Arbiansah (Siliwangi University, 2018)
Pedagogical decisions and teaching practice are influenced by student teachers’ belief. Personal predispositions of student teachers’ beliefs on teaching practice are strongly affected by their experiences, or course content they have been taken. In developing their beliefs, values, and practice of teaching, student teachers adopt theories about good teaching practice by interpreting these experiences in teaching or taking courses. The numbers of studies have been conducted about student teachers’ belief on teaching practice from their experiences in teaching-learning, but less attention put on student teachers’ belief in interpreting their pedagogical knowledge from theories to practices. Thus, to fill the gap, the writers conduct a case study regarding to a student teacher’s belief after she had received pedagogical courses and finished preservice teaching program. Using a thematic analysis from a semi structured interview and reflective journal from a student teacher in English Education Department in Tasikmalaya, the researchers examined the student teacher’s belief based on her experiences in pre-service teaching program. The overall contribution of this study is to evaluate student teachers’ teaching belief with the principle of teaching given in the class, since teaching belief is significant to personal development of pre-service teachers.